Acculturative stress and university life adjustment among international students in China: the moderating role of perceived social support - Chen, Hang (Frontiers in Psychology, 2025)
This study examines how acculturative stress influences international students’ adjustment to university life in China, with a particular focus on the moderating role of perceived social support. Drawing on a sample of 642 international students, hierarchical regression and interaction analyses reveal that acculturative stress significantly impairs emotional, social, and academic adjustment. However, perceived social support buffers these effects, especially in emotional domains. These findings contribute to the literature on cross-cultural adaptation and underscore the importance of institutional and interpersonal support systems for student wellbeing.